Collaborative control technology and application of support and modification for soft-rock roadway in a kilometer-deep coal mine - En Wang; Shuaifeng Yin; Xuexi Chen; Ze Gao; Aiguo Sun; Yitao Yan (Scientific Reports)
Abstract The soft-rock roadways in kilometer-deep coal mines are often damaged by large deformation and have to be periodically expanded and repaired, which seriously restricts the safe and efficient production of coal mines. A typical soft-rock roadway in a kilometer-deep coal mine is selected as the engineering, and the main reasons for roadway deformation are analyzed, and the ground stress and mechanical characteristics are obtained. The Flac3D numerical model, which can accurately reflect the deformation characteristics of surrounding rock in kilometer-deep soft-rock roadway, has been constructed, and the evolution laws of stress field and its damage mechanism have been analyzed with the vertical stress, vertical displacement and plastic zone. The damage range of roadway surrounding rock is elucidated by endoscopic observation, and the synergistic control technology of support and modification is proposed. The on-site engineering application is carried out in Qianyingzi Coal Mine, and the results show that the collaborative control technology of support and modification ensures the safety and stability of deep soft-rock roadway. The results provide important and preliminary technical references for realizing safe and intelligent mining in coal mines.